Correlation between the chemical, microbiological and sensory characteristics of cream cheese using a mixed and single probiotic culture - Tologana, Ria Dewiyanti (Springer, 2023)
The use of mixed culture in the fermentation industry requires more complicated equipment, processes, and monitoring systems; therefore, a single culture may be preferable. This study aimed to investigate the correlation between chemical and microbiological properties and sensory characteristics. In addition, this study aimed to determine the different characteristics of cheese made using single probiotic cultures of Lactobacillus plantarum Dad-13 and Lactobacillus plantarum Kita-3 and mixed culture. The obtained results showed that the chemical characteristics of cream cheese made using single cultures were similar to those of cream cheese made using mixed cultures. The viability of the cells remained high after 35Â days of storage for the single culture, which was not the case for the mixed culture. In terms of sensory analysis, cream cheese made using the single culture L. plantarum Kita-3 showed higher overall liking score among the samples, which might correlate with the high ester and ketone content. In addition, there was a strong relationship between the ethyl octanoate and methyl butanol contents and the overall liking score. The results of this study showed that the use of a single culture of L. plantarum Kita-3 could improve the sensory characteristics of cream cheese with probiotic properties. This study also contributed to the development of cream cheese production, particularly in the screening of potential starters. Â© 2022, Association of Food Scientists & Technologists (India).